PERANAN TRYPTOPHAN DAN KONSENTRASI AWAL INOKULAN DALAM PENINGKATAN KANDUNGAN IAA, NITROGEN TOTAL DAN KEPADATAN SEL PADA PUPUK HAYATI CAIR Azospirillum - Danapriatna, Nana (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2013)
Inoculant with N2 fixation capacity and optimal cell density and the concentration of precursor in the synthesis of growth hormone is required in the production process of liquid biofertilizers Azospirillum. This experiment was conducted in order to study the effect of the combination of the concentration of tryptophan as precursors and initial concentration of inoculants Azospirillum to the increased production of hormones, nitrogen, and the cell density of liquid biofertilizers. Completely randomized design with nine treatment combinations initial concentration inoculant (5, 10 and 15%) and the concentration of tryptophan (without, 50 and 100 g mL-1) with three replications was used in this study. The results showed a positive effect occurs from the initial inoculum concentration Azospirillum and tryptophan concentration on nitrogen and production of IAA, but has no effect on cell density Azospirillum. The technology to manufacture biofertilizer liquid inoculant Azospirilum with an initial concentration of 10% and 50 g ml-1 tryptophan is the best combination in producing of liquid biofertilizer.